2015
DOI: 10.1155/2015/585230
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Similarity Laws for Local Damage Effects in a Concrete Target under the Impact of Projectiles

Abstract: The local destruction and deformation characteristics of a concrete target impacted by a rigid projectile were analyzed, and the similarity laws for local damage effects in the concrete target were studied utilizing the rigid-plastic, internal friction, and modified hydrodynamic models. For a thin target, the impact factor is the only factor controlling the low-velocity impact process. For a thick target impacted by a projectile at intermediate velocity, internal friction is the main factor contributing to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Jiang et al 31 studied the scaled collision law of a metal cone specimen. Wang et al 32 studied local damage effects in a concrete target under the impact of projectiles. Xu et al 33 showed that scaled models represent real models if appropriate similarity coefficients are applied.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al 31 studied the scaled collision law of a metal cone specimen. Wang et al 32 studied local damage effects in a concrete target under the impact of projectiles. Xu et al 33 showed that scaled models represent real models if appropriate similarity coefficients are applied.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete is an important material which can be used to construct protective structure to resist impact by projectiles and explosive loads [1,2]. Much work has been done to investigate the effects of concrete targets subject to projectile impact, such as Guirgis and Guirguis [3], Wang et al [4], Yu et al [5], Bian et al [6], and Wen and Lan [7]. However, most of the work was conducted to predict resistance/strength of reinforced concrete targets.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al studied scaled collision law of metal cone specimen [20]. Wang et al studied local damage effects in a concrete target under the impact of projectiles [21]. Xu et al showed that scaled models represent real models if appropriate similarity coefficients are applied [22].…”
Section: Introductionmentioning
confidence: 99%